An organic cuprous halide framework material, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611469762.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]利用光催化剂吸收太阳能驱动水分解产氢是实现太阳能向化学能转化的理想途径,在应对全球能源危机与环境挑战方面具有重大潜力,在众多光催化材料中,无机-有机杂化金属卤化物凭借其优异的光电性能、可调的带隙结构以及简便的溶液加工性,作为一类新兴的光催化剂受到广泛关注;然而,该类材料中严重的载流子复合问题制约了其光催化效率;同时,其离子晶体的本质使其在水相体系中极易发生水解坍塌,难以满足实际应用对稳定性的要求
(1)极端条件下的超高稳定性:本发明以强配位键构筑三维框架,所得材料能够稳定存在于pH=4-10的水溶液以及沸水中,克服了传统卤化物光催化剂遇水分解的缺陷。
Smart Images

Figure CN122978466A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of crystal materials and photocatalysis technology, specifically relating to an organic halide cuprous framework material, its preparation method, and its application. Background Technology
[0002] Utilizing photocatalysts to absorb solar energy and drive water splitting to produce hydrogen is an ideal way to convert solar energy into chemical energy, and it has great potential in addressing the global energy crisis and environmental challenges. Among many photocatalytic materials, inorganic-organic hybrid metal halides have attracted widespread attention as an emerging class of photocatalysts due to their excellent photoelectric properties, tunable bandgap structure, and simple solution processability. However, the severe carrier recombination problem in these materials restricts their photocatalytic efficiency. At the same time, their ionic crystal nature makes them extremely prone to hydrolysis and collapse in aqueous systems, making it difficult to meet the stability requirements of practical applications.
[0003] Metal halide coordination polymers, which use metal halide clusters as secondary building blocks and are linked by coordination bonds, are a new type of inorganic-organic hybrid metal halide materials. They not only retain the excellent photoelectric properties of metal halide structural units, but also significantly improve the chemical and water stability of the materials due to the stable coordination network, overcoming the defect of traditional ionic metal halides decomposing upon contact with water. However, similar to most semiconductor photocatalysts, these coordination polymers still face the bottleneck of rapid recombination of photogenerated carriers, resulting in their catalytic activity being far lower than theoretically expected.
[0004] Built-in electric fields have been proven to be an effective means of driving the separation of photogenerated carriers, especially in non-centrosymmetric piezoelectric materials. External mechanical stress can induce a dynamic built-in electric field, providing a continuous and tunable driving force for charge separation. Introducing built-in electric fields into metal halide coordination polymer systems is expected to significantly improve charge separation and transport efficiency while maintaining their high stability and excellent photoelectric properties, thereby enhancing photocatalytic hydrogen production activity. Therefore, designing and synthesizing metal halide framework materials with non-centrosymmetric structures to achieve efficient coupling between the piezoelectric effect and the photocatalytic process to obtain excellent piezoelectric photocatalytic performance has become a research focus in this field and is one of the current cutting-edge directions both domestically and internationally. Summary of the Invention
[0005] This invention aims to provide an organic halide cuprous framework material, its preparation method, and its application. It has a wide visible light absorption range and a suitable redox potential. At the same time, the non-centrosymmetric structure endows the material with inherent piezoelectric properties, which has important application value in the field of photocatalytic water splitting for hydrogen production.
[0006] To achieve the above objectives, the present invention provides the following technical solution: an organohalogenated cuprous framework material, wherein the framework material is composed of cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole, wherein the molar ratio of cuprous halide to 3,5-dimethyl-4H-1,2,4-triazole is 0.42 : (0.25-1). The chemical formula of the framework material is [Cu4X](dmtz)3, where X is Br or I, and dmtz is 3,5-dimethyl-4H-1,2,4-triazole.
[0007] In a preferred embodiment, the framework material belongs to the hexagonal crystal system with a non-centrosymmetric space group of P63. It consists of umbrella-shaped [Cu4X] clusters as secondary structural units, with six dmtz ligands connecting each cluster to form a three-dimensional framework containing one-dimensional channels. The Cu4X clusters are bridged by the μ4- halogen atoms at the top. Each [Cu4X] cluster secondary building unit is further connected by three dmtz ligands to form a three-dimensional framework structure with one-dimensional channels.
[0008] In a preferred embodiment, the framework material contains two crystallographically independent copper centers, all of which are in a μ4 configuration. The first copper center adopts a tridentate coordination configuration and is bonded to the central halogen atom and two triazole nitrogen atoms from two dmtz ligands. The second copper center adopts a tetrahedral coordination configuration and is bonded to the same central halogen atom and three triazole nitrogen atoms from three dmtz ligands.
[0009] A method for preparing an organic cuprous halide framework material includes the following steps: S1. First, weigh out appropriate amounts of cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole, and then add the cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole to the reaction vessel in sequence. S2. Then, N,N-dimethylacetamide (DMA) solvent is added to the reaction vessel of S1 and mixed. The reaction vessel containing the mixture is then placed in an oven and heated to the required temperature for a period of time. S3. After the reaction is complete, cool the mixture to the required temperature, then collect the resulting pale yellow blocky crystals by filtration, and wash them three times alternately with N,N-dimethylformamide (DMF) and water. Finally, dry the mixture in a 60 ℃ constant temperature oven to obtain the required framework material.
[0010] In a preferred embodiment, the reactor is a 15 mL polytetrafluoroethylene-lined high-pressure reactor.
[0011] In a preferred embodiment, the ratio of the added cuprous halide to N,N-dimethylacetamide is 0.42 mmol : (5~50) mL.
[0012] In a preferred embodiment, the temperature of the heating reaction in step S2 is 100~200℃.
[0013] In a preferred embodiment, the heating reaction time in step S2 is 10-100 h.
[0014] In a preferred embodiment, the heating and cooling rates are both (20-25) °C / h.
[0015] Application of an organic halide cuprous framework material as a catalyst for piezoelectric photocatalytic water splitting to produce hydrogen.
[0016] Compared with the prior art, the beneficial effects of the present invention are: (1) Ultra-high stability under extreme conditions: The present invention constructs a three-dimensional framework with strong coordination bonds, and the resulting material can exist stably in aqueous solutions with pH=4-10 and boiling water, overcoming the defect of traditional halide photocatalysts decomposing in water.
[0017] (2) Ultra-high hydrogen production activity enhanced by piezoelectric response: The material of the present invention has a non-centrosymmetric structure, which can generate a piezoelectric built-in electric field under ultrasonic vibration, which greatly promotes the separation of bulk charge. Under the dual excitation of visible light and ultrasound, an extremely high photocatalytic hydrogen evolution rate can be achieved without the need for a noble metal co-catalyst.
[0018] (3) Precise control of halogen substitution strategy: Substitution from Br to I not only narrows the optical band gap of the material and broadens the absorption of visible light, but also induces greater local polarization, significantly improves the piezoelectric coefficient, and realizes the simultaneous optimization of optical and piezoelectric properties. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the crystal structure and local coordination environment of [Cu4Br](dmtz)3 prepared in Example 1 of the present invention; Figure 2 The X-ray powder diffraction patterns of [Cu4Br](dmtz)3 prepared in Example 1 of this invention after being treated under different conditions; Figure 3 The Taucplot of the UV-Vis diffuse reflectance data of [Cu4Br](dmtz)3 prepared in Example 1 of this invention; Figure 4 The piezoelectric response force microscopy (PFM) amplitude and phase diagram of [Cu4Br](dmtz)3 prepared in Example 1 of this invention; Figure 5 The graph shows the hydrogen production of [Cu4Br](dmtz)3 prepared in Example 1 of this invention as a function of time under pure light irradiation and under dual excitation conditions of light and ultrasound. Figure 6 This is a schematic diagram of the crystal structure and local coordination environment of [Cu4I](dmtz)3 prepared in Example 2 of the present invention; Figure 7 The X-ray powder diffraction patterns of [Cu4I](dmtz)3 prepared in Example 2 of this invention after being treated under different conditions; Figure 8 The Taucplot of the UV-Vis diffuse reflectance data of [Cu4I](dmtz)3 prepared in Example 2 of this invention; Figure 9 The piezoelectric response force microscopy (PFM) amplitude and phase diagram of [Cu4I](dmtz)3 prepared in Example 2 of this invention; Figure 10 The graph shows the hydrogen production of [Cu4I](dmtz)3 prepared in Example 2 of this invention as a function of time under pure light irradiation and under dual excitation conditions of light and ultrasound. Figure 11 This is a schematic diagram of the crystal structure and local coordination environment of [Cu4X](dmtz)3 of the present invention. Detailed Implementation
[0020] Please see Figures 1-11 To further illustrate the technical means and effects of the present invention in order to achieve the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.
[0021] In the following embodiments, unless otherwise specified, the raw materials or processing techniques are conventional commercially available materials or processing techniques in the art.
[0022] Example 1: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.50 mmol) of 3,5-dimethyl-4H-1,2,4-triazole (dmtz) and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Then add 7.5 mL of N,N-dimethylacetamide (DMA) solvent, mix, and place the reactor in an oven. Heat at 180 °C for 3 days (72 hours). After the reaction is complete, allow the system to cool naturally to room temperature. Collect the resulting pale yellow blocky crystals by filtration and wash them three times alternately with N,N-dimethylformamide (DMF) and water. Then dry them in a 60 °C oven.
[0023] The material obtained in this embodiment is a pale yellow blocky crystal. Single-crystal X-ray diffraction characterization confirmed that the material belongs to the hexagonal noncentrosymmetric space group. P 63, possesses Figure 1 The structure shown.
[0024] Stability study of material [Cu4Br](dmtz)3: Weigh three portions (0.1g each) of the sample from this embodiment and soak them respectively in a dilute hydrochloric acid solution (pH=4), a sodium hydroxide solution (pH=10), and boiling water for 24 hours. After filtering and washing the residue, characterize the crystallinity of the residue using X-ray powder diffraction (PXRD). Compare the PXRD of the residue with that of the untreated sample. Figure 2 As shown, the identical PXRD patterns demonstrate that the sample in this embodiment has high structural stability.
[0025] It should be noted that: Figure 2 The horizontal axis represents the diffraction angle (2θ) of the X-ray diffraction, and the vertical axis represents the relative diffraction intensity.
[0026] Band structure determination of material [Cu4Br](dmtz)3: The obtained crystalline material was ground into powder, and 0.5g was weighed out. Its ultraviolet-visible diffuse reflectance absorption spectrum was measured, such as... Figure 3 As shown, the light absorption of the material extends into the visible light region, with an absorption band edge of 500 nm and a band gap of 2.32 eV, indicating that the material has the potential to absorb sunlight for photocatalysis.
[0027] It should be noted that: Figure 3 The horizontal axis represents energy (eV) (eV: electron volt, a unit of energy), and the vertical axis indicates that the material belongs to an indirect bandgap semiconductor.
[0028] Piezoelectricity determination of material [Cu4Br](dmtz)3: The piezoelectric properties of the material were characterized using piezoelectric response force microscopy. For example... Figure 4 As shown, when the bias voltage is swept from -50 V to 50 V, a reversal of nearly 180° in the polarization vector is observed, and a typical butterfly-shaped amplitude ring appears, which clearly confirms its inherent piezoelectricity.
[0029] It should be noted that: Figure 4 The horizontal axis represents the DC bias voltage (volts), the left vertical axis represents the amplitude (nanometers), specifically represented by the gray line segment in the figure, and the right vertical axis represents the phase (degrees), specifically represented by the black line segment in the figure.
[0030] Determination of piezoelectric photocatalytic hydrogen production performance of material [Cu4Br](dmtz)3: 0.015 g of [Cu4Br](dmtz)3 photocatalyst and 0.03 g of fluorescein were weighed and placed at the bottom of the photocatalytic reactor. Then, 60 mL of a mixed solvent of water and ethanol containing 10% triethylamine was added. The system was then subjected to dual treatment with a xenon lamp and ultrasound. The generated H2 was qualitatively and quantitatively analyzed by gas chromatography. The photocatalytic efficiency is shown in the figure below. Figure 5 As shown, this system can achieve excellent piezoelectric photocatalytic hydrogen production performance.
[0031] It should be noted that: Figure 5 The horizontal axis represents time (hours); the vertical axis represents hydrogen production (millomoles / gram).
[0032] Example 2: Using the same synthesis method as in Example 1, except that the precursor was replaced with an equimolar ratio of cuprous iodide, 0.06 g (0.42 mmol) of cuprous iodide (CuI) and 0.05 g (0.50 mmol) of 3,5-dimethyl-4H-1,2,4-triazole (dmtz) were weighed, 7.5 mL of DMA solvent was added, and the reaction was carried out at 180 °C for 3 days (i.e. 72 hours). After cooling, filtration and washing with DMF and water, yellow blocky crystals [Cu4I](dmtz)3 were obtained.
[0033] The material obtained in this embodiment is a pale yellow blocky crystal. Single-crystal X-ray diffraction characterization confirmed that the material belongs to the hexagonal noncentrosymmetric space group. P 63, possesses Figure 6 The structure shown.
[0034] Stability study of material [Cu4I](dmtz)3: Five portions (0.1g each) of the sample from this embodiment were weighed and soaked in dilute hydrochloric acid solution (pH=4), sodium hydroxide solution (pH=10), water, and boiling water, respectively, for 24 hours. The residues were filtered, washed, and their crystallinity was characterized by X-ray powder diffraction (PXRD). The PXRD values were compared with those of the untreated sample. Figure 7 As shown, the identical PXRD patterns demonstrate that the sample in this embodiment has high chemical and thermal stability.
[0035] It should be noted that: Figure 7 The horizontal axis represents the diffraction angle (2θ) of the X-ray diffraction, and the vertical axis represents the relative diffraction intensity.
[0036] Band structure determination of material [Cu4I](dmtz)3: The obtained crystalline material was ground into powder, and 0.5g was weighed out. Its ultraviolet-visible diffuse reflectance absorption spectrum was measured, such as... Figure 8 As shown, the light absorption of the material extends into the visible light region, with an absorption band edge of 500 nm and a band gap of 2.32 eV, indicating that the material has the potential to be used for photocatalysis with sunlight.
[0037] It should be noted that: Figure 8 The horizontal axis represents energy (eV) (eV: electron volt, a unit of energy), and the vertical axis indicates that the material belongs to an indirect bandgap semiconductor.
[0038] Piezoelectricity determination of material [Cu4I](dmtz)3: The piezoelectric properties of the material were characterized using piezoelectric response force microscopy. For example... Figure 9 As shown, when the bias voltage is swept from -50 V to 50 V, a near 180° reversal of the polarization vector is observed, and a typical butterfly-shaped amplitude ring appears, which clearly confirms its inherent piezoelectricity. Compared to [Cu4Br](dmtz)3, [Cu4I](dmtz)3 exhibits a larger amplitude variation and a narrower phase reversal, indicating that [Cu4I](dmtz)3 has stronger piezoelectricity.
[0039] It should be noted that: Figure 9 The horizontal axis represents the DC bias voltage (volts), the left vertical axis represents the amplitude (nanometers), specifically represented by the gray line segment in the figure, and the right vertical axis represents the phase (degrees), specifically represented by the black line segment in the figure.
[0040] Determination of piezoelectric photocatalytic hydrogen production performance of material [Cu4I](dmtz)3: 0.015 g of [Cu4I](dmtz)3 photocatalyst and 0.03 g of fluorescein were weighed and placed at the bottom of the photocatalytic reactor. Then, 60 mL of a mixed solvent of water and ethanol containing 10% triethylamine was added. The system was then subjected to dual treatment with a xenon lamp and ultrasound. The generated H2 was qualitatively and quantitatively analyzed by gas chromatography. The photocatalytic efficiency is shown in the figure below. Figure 10 As shown, it can be concluded that this system can simultaneously achieve photocatalytic CO2 reduction and water oxidation.
[0041] It should be noted that: Figure 10 The horizontal axis represents time (hours); the vertical axis represents hydrogen production (millomoles / gram).
[0042] Comparative Example 1: The reaction was largely the same as in Examples 1 or 2, except that the temperature of the solvothermal reaction was changed to 60 °C. After the reaction, the target product was not obtained. This is because the synthesis temperature was too low to allow CuX and the dmtz ligand to self-assemble into the target structure.
[0043] Comparative Example 2: The process was largely the same as in Examples 1 or 2, except that the temperature of the solvothermal reaction was changed to 280 °C. After the reaction, an amorphous product was obtained. This is because the synthesis temperature was too high, exceeding the tolerance limit of the organic ligands or coordination bonds, leading to structural collapse or thermal decomposition of the ligands.
[0044] Comparative Example 3: The reaction was largely the same as in Examples 1 or 2, except that the amount of 3,5-dimethyl-4H-1,2,4-triazole (dmtz) was changed to 0.003 g. After the reaction, a large amount of unreacted CuX precipitated. Due to the low concentration of the organic ligand, it was unable to form effective competitive coordination with the central halogen atom, thus failing to support the full extension of the three-dimensional channel structure.
[0045] Comparative Example 4: The reaction was largely the same as in Example 1 or 2, except that the amount of 3,5-dimethyl-4H-1,2,4-triazole (dmtz) was changed to 0.40 g. After the reaction, a large amount of unreacted organic ligands and halogen-free coordination polymers were obtained. Excess ligands alter the coordination equilibrium of the system, making it difficult for halogens to coordinate with Cu.
[0046] Comparative Example 5: The results were largely the same as in Examples 1 or 2, except that the solvent DMA was changed to 0.1 mL in this comparative example. The target product was not obtained after the reaction was complete. This is because the solvent was too insufficient; the reactants did not dissolve, and the target structure could not be obtained.
[0047] Comparative Example 6: The process was largely the same as in Examples 1 or 2, except that the solvent DMA was changed to 55 mL in this comparative example. The target product was not obtained after the reaction. This is because too much solvent hindered nucleation, preventing the formation of the target structure.
[0048] Comparative Example 7: The results are largely the same as in Examples 1 or 2. In this comparative example, the reaction time was changed to 5 h. Due to the short reaction time, the target product was not obtained after the reaction was completed.
[0049] Comparative Example 8: The results were largely the same as in Examples 1 or 2, except that the reaction time was changed to 110 h. The target product was not obtained after the reaction was completed. This is because the reaction time was too long, and the target crystals may have redissolved in the mother liquor.
[0050] Example 3: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.005 g (0.05 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0051] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0052] Example 4: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.35 g (3.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0053] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0054] Example 5: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 0.3 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0055] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0056] Example 6: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 50 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0057] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0058] Example 7: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 80 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0059] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0060] Example 8: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 250 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 4 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0061] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0062] Example 9: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 0.1 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0063] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0064] Example 10: Weigh 0.06 g (0.42 mmol) of cuprous bromide (CuBr) and 0.05 g (0.5 mmol) of dmtz, and place them in a 15 mL polytetrafluoroethylene-lined high-pressure reactor. Add 7.5 mL of DMA solvent. After mixing, heat the mixture at 180 °C for 72 hours. After the reaction is complete, cool the system to 20 °C at a rate of 25 °C / hour to obtain yellow blocky crystals [Cu4Br](dmtz)3.
[0065] Similarly, by replacing the precursor with an equimolar amount (0.42 mmol) of cuprous iodide (CuI), and with all other operations and parameters exactly the same, the target product [Cu4I](dmtz)3 with high purity was obtained after the reaction.
[0066] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. An organic cuprous halide framework material, characterized in that: The framework material is composed of cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole, wherein the molar ratio of cuprous halide to 3,5-dimethyl-4H-1,2,4-triazole is 0.42 : (0.25-1). The chemical formula of the framework material is [Cu4X](dmtz)3, where X is Br or I, and dmtz is 3,5-dimethyl-4H-1,2,4-triazole.
2. The organic halide cuprous framework material according to claim 1, characterized in that: The framework material belongs to the hexagonal crystal system with a non-centrosymmetric space group of P63. It consists of umbrella-shaped [Cu4X] clusters as secondary structural units, and six dmtz ligands connect the clusters to form a three-dimensional framework with one-dimensional channels.
3. An organohalogenated cuprous framework material according to claim 1 or 2, characterized in that: The framework material contains two crystallographically independent copper centers, and all halogens are in the μ4 configuration.
4. A method for preparing an organohalogenated cuprous framework material, applied to the organohalogenated cuprous framework material as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. First, weigh out appropriate amounts of cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole, and then add the cuprous halide and 3,5-dimethyl-4H-1,2,4-triazole to the reaction vessel in sequence. S2. Then, N,N-dimethylacetamide (DMA) solvent is added to the reaction vessel of S1 and mixed. The reaction vessel containing the mixture is then placed in an oven and heated to the required temperature for a period of time. S3. After the reaction is complete, cool the mixture to the required temperature, then collect the resulting pale yellow blocky crystals by filtration, and wash them three times alternately with N,N-dimethylformamide (DMF) and water. Finally, dry the mixture in a 60 ℃ constant temperature oven to obtain the required framework material.
5. The method for preparing an organic halide cuprous framework material according to claim 4, characterized in that: The reactor is a 15 mL polytetrafluoroethylene-lined high-pressure reactor.
6. The method for preparing an organic halide cuprous framework material according to claim 4, characterized in that: The ratio of the amount of cuprous halide to N,N-dimethylacetamide added is 0.42 mmol : (5~50) mL.
7. The method for preparing an organic halide cuprous framework material according to claim 4, characterized in that: In step S2, the temperature of the heating reaction is 100~200℃.
8. The method for preparing an organic halide cuprous framework material according to claim 4, characterized in that: In step S2, the heating reaction takes 10 to 100 hours.
9. The method for preparing an organic halide cuprous framework material according to claim 4, characterized in that: The heating and cooling rates are both (20-25) °C / h.
10. The application of the organohalide cuprous framework material according to any one of claims 1-3, characterized in that, The framework material is used as a catalyst for piezoelectric photocatalytic water splitting to produce hydrogen.